A Detoxification-Free Process for Enhanced Ethanol Production From Corn Fiber Under Semi-Simultaneous Saccharification and Fermentation - Guo, Yingjie; Huang, Jiamin; Xu, Nuo; Jia, Hexue; Li, Xuezhi; Zhao, Jian; Qu, Yinbo (Frontiers in Microbiology, 2022)
Corn fiber, a by-product from the corn-processing industry, is an attractive feedstock for cellulosic ethanol because of its rich carbohydrate content (mainly residual starch, cellulose, and hemicellulose), abundant reserves, easy collection, and almost no transportation cost. However, the complex structure and components of corn fiber, especially hemicellulose, make it difficult to be effectively hydrolyzed into fermentable sugars through enzymatic hydrolysis. This study developed a simple and easy industrialized process without detoxification treatment for high-yield ethanol produced from corn fiber. Corn fiber was pretreated by dilute acid under the conditions optimized by Box-Behnken design (0.5% H2SO4 at 105°C for 43 min), and 81.8% of total sugars, including glucose, xylose, and arabinose, could be recovered, then the mixture (solid and hydrolysates) was directly used for semi-simultaneous saccharification and fermentation without detoxification, and ethanol yield reached about 81% of the theoretical yield.